Efficacy and safety of octreotide treatment for diazoxide‐unresponsive congenital hyperinsulinism in China - Bingyan Cao; Wu Di; Chang Su; Jiajia Chen; Xuejun Liang; Min Liu; Wenjing Li; Xiaoqiao Li; Chunxiu Gong (Wiley, 2020)
ABSTRACT Importance Octreotide is an off‐label medicine for congenital hyperinsulinism (CHI), but is currently widely used for treatment of patients with CHI. Thus far, variable efficacy and adverse effects have been reported for octreotide. Objective The present study evaluated the efficacy and safety of a subcutaneous octreotide injection for treatment of diazoxide‐unresponsive CHI in China. Methods This study was a retrospective review of children with diazoxide‐unresponsive CHI who were treated with a subcutaneous octreotide injection. The efficacy and side effects of the treatment were assessed. Results Twenty‐five Chinese children (15 boys) were involved in the study. Their median age at diagnosis was 8 weeks (range, 1-24 weeks) and median age at the final follow‐up was 1.8 years (range, 0.3-3.3 years). Octreotide therapy effectively increased blood glucose levels in all patients. The intravenous glucose infusion rate was reduced in all patients. Twenty‐one patients gradually discontinued the intravenous glucose infusion while receiving octreotide combined with frequent carbohydrate/glucose‐rich feeding. Among patients with a monoallelic ATP‐sensitive potassium (KATP) channel mutation, 50.0% showed gradual remission during follow up, indicating that the octreotide treatment may be a feasible alternative to surgery, especially for patients with monoallelic KATP‐channel mutations. Transient elevation of liver enzymes occurred in 20.0% of patients, while asymptomatic gallbladder pathology occurred in one patient. The growth rates of these patients were normal (height standard deviation score was 0.3 ± 1.5 at the final follow‐up). Interpretation Octreotide was a well‐tolerated, effective therapy for most children with diazoxide‐unresponsive CHI.